The determinants of consumer’s intention on purchasing houses in Seremban, Negeri Sembilan / Nur Hidayatul Hidayu Hashim and Nurul Hazwani Zainal Abidin - Hashim, Nur Hidayatul Hidayu; Zainal Abidin, Nurul Hazwani (Faculty of Business and Management, 2014)
The purpose of this study is to determine the factors affecting consumer’s intention on purchasing houses in Seremban, Negeri Sembilan. For this study only 200 respondents managed to be collected using convenience sampling. The objectives of this study is to identify the determinants of consumer’s intentions on purchasing house in Seremban, Negeri Sembilan to ascertain the best predictor that affect consumer’s intentions on purchasing house in Seremban, Negeri Sembilan. This study is a quantitative study whereby the findings the findings of the study were analysed using Statistical Package for the Social Sciences (SPSS). There five analysis used in this study to analyze the data which is Reliability Analysis, Frequency Analysis, Descriptive Analysis, Pearson Correlation Analysis and also Multiple Regression Analysis to achieved research objective. From the study most of the respondents were male, married and most of the respondents have household monthly income range between RM1001-RM3000. From this study, it can be concluded that most of the respondents is male, married and works for above 10 years in organisations. In addition, multiple regressions also answer research objective that strategic location and government policy influences consumer’s intention on purchasing houses since its P-values is less than 0.05.